Littérature et savoir. De la flaubertologie quenienne à l’invention du roman - Daniela Tononi (Flaubert: Revue Critique et Génétique)
The research that Queneau did at the Bibliothèque nationale to write his work on the Fous Littéraires was intertwined with the writing of Derniers jours, Les Enfants du Limon and various theoretical and erudite texts by the Oulipo writer. Through his novels, the analysis of some pretextual documents and the reading of the text on the Fous, only published in 2002 in the original version that preceded its incorporation into Les Enfants du Limon, demonstrate the influence of the Flaubertian model — and of the novel Bouvard et Pécuchet in particular — in Raymond Queneau’s work. In this article we will demonstrate, through the interpretation of his theoretical texts and narrative discoveries, that different formal and aesthetic elements of Queneau’s novel are reformulations of certain aspects of Flaubert’s encyclopaedism.